2019
DOI: 10.1002/sdtp.12987
|View full text |Cite
|
Sign up to set email alerts
|

42‐3: Novel Transparent Screen Combined with Light Guide System

Abstract: We have successfully developed a novel transparent screen leading to a new AR display without unexpected light, combining with a light guide system. We believe this novel AR display could expand applications into show window and vehicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In our previous study, we found there was a relationship between the tilt angle of cholesteric liquid crystals and the surface energy acting in polar angles [6]. In this study, we designed the surface energy at the air interface and at the substrate interface independently to achieve different tilt angle at the air interface and at the substrate interface (φ sub > φ air ).…”
Section: Figure 9 Relationship Between Tilt Angle φ and Dmentioning
confidence: 96%
“…In our previous study, we found there was a relationship between the tilt angle of cholesteric liquid crystals and the surface energy acting in polar angles [6]. In this study, we designed the surface energy at the air interface and at the substrate interface independently to achieve different tilt angle at the air interface and at the substrate interface (φ sub > φ air ).…”
Section: Figure 9 Relationship Between Tilt Angle φ and Dmentioning
confidence: 96%